2017
DOI: 10.3389/fphar.2017.00684
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacodynamic Evaluation and PK/PD-Based Dose Prediction of Tulathromycin: A Potential New Indication for Streptococcus suis Infection

Abstract: Tulathromycin is the first member of the triamilide antimicrobial drugs that has been registered in more than 30 countries. The goal of this study is to provide a potential new indication of tulathromycin for Streptococcus suis infections. We investigated the pharmacokinetic and ex vivo pharmacodynamics of tulathromycin against experimental S. suis infection in piglets. Tulathromycin demonstrated a relatively long elimination half-life (74.1 h) and a mean residence time of 97.6 h after a single intramuscular a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
22
3

Year Published

2019
2019
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(33 citation statements)
references
References 31 publications
8
22
3
Order By: Relevance
“…This difference in susceptibility agreed with the previous findings, in which a similar 4 to 16-fold reduction in tildipirosin MIC was observed for A. pleuropneumoniae by addition of 50% serum to broth medium [14]. More recently, our study regarding tulathromycin demonstrated that incorporation of increasing proportion of serum to broth from 25 to 75% progressively reduced the MIC against S. suis [13].…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…This difference in susceptibility agreed with the previous findings, in which a similar 4 to 16-fold reduction in tildipirosin MIC was observed for A. pleuropneumoniae by addition of 50% serum to broth medium [14]. More recently, our study regarding tulathromycin demonstrated that incorporation of increasing proportion of serum to broth from 25 to 75% progressively reduced the MIC against S. suis [13].…”
Section: Discussionsupporting
confidence: 92%
“…The AUC 24h /MIC targets for gamithromycin against H. parasuis associated with bactericidal and eradication effects were 30.3 h and 41.2 h, respectively. This microbiological response in ex vivo PK/PD model was similar to or in excess of previously approved veterinary macrolides such as tulathromycin and tildipirosin [13,23].…”
Section: Discussionsupporting
confidence: 70%
See 3 more Smart Citations